Epidermolysis bullosa pruriginosa: A report of two cases - Varadraj Vasant Pai; Tukaram Sori; Kikkeri Narayanshetty Naveen; Sharatchandra Bhimrao Athanikar; Vijetha Rai; Dinesh Udupi Shastry (Wolters Kluwer Medknow Publications, 2014)
Epidermolysis bullosa (EB) pruriginosa is a very rare pattern of dystrophic EB caused by type VII collagen gene mutation, with distinctive clinico-pathological features. It is characterized by nodular prurigo-like lichenified lesions, nail dystrophy, and variable presence of albopapuloid lesions. We report two such cases.